Peningkatan Keterampilan Membuat Alat Peraga Matematika Pada Mahasiswa Prodi PGSD Universitas Peradaban - Adi Candra Kusuma; Anggraeni Mashinta Sulistyani; Eka Trisnawati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
In understanding abstract mathematical concepts, students need teaching aids such as concrete objects as an intermediary or visualization. The purpose of the research is to obtain skills in making mathematics teaching aids on PGSD University of Civilization students. The research method uses qualitative research with a total of 66 research subjects in the third semester of 2015/2016 Academic Year. Data collection techniques were taken using observation, interviews, documentation. The results obtained from the study provide knowledge of new knowledge, improve skills in making learning support instruments, train the creative thinking of students of the University of Civilization PGSD as a provision of learning strategies when going to be a teacher. This training prepares prospective teachers in explaining mathematical concepts, in learning mathematics, the use of teaching aids is expected to increase student motivation. Motivation can arise because many ideas and new ideas and fun learning contains a variety of information that is relevant to the learning needs of students.